The Changing Nature and Definitions of Industrial Design and Implications for Prospective Undergraduate Students - Goatman, Mike; Moody, Louise (Design and Technology Education: An International Journal, 2014)
There are currently a wide range of Higher Education Industrial Design courses available in the UK. In the present era, a wider breadth of narrative has developed within the subject, and as a result the content of industrial design educational offerings varies considerably. The paper assesses the industry view of Industrial Design as a discipline from the perspective of those employing university graduates. These views illustrate a change in the discipline, and this is considered in respect to current education practice. The choice of entry courses for the student wishing to embark on a career in the subject has also widened. It is argued that at present, the access to courses offers a haphazard informational stream to the potential applicant. An approach to developing an online facility to enable potential students to apply for the right course is discussed. It is suggested that a consistent and comparable platform of guidance is needed by which potential students can identify and match the course offering against their aptitudes and aspirations. A framework for such a system is proposed. Given that course choice will ultimately define the nature of their career opportunities it is argued that this would be a useful and productive asset.